EFEKTIVITAS PENGGUNAAN ALAT PERAGA MODEL BANGUN DATAR TERHADAP HASIL BELAJAR SISWA DALAM MEMAHAMI KONSEP SEGITIGA : EFEKTIVITAS PENGGUNAAN ALAT PERAGA MODEL BANGUN DATAR TERHADAP HASIL BELAJAR SISWA DALAM MEMAHAMI KONSEP SEGITIGA - Asshifa, Jilan Najwa; Subroto, Prawidi Wisnu; Tunisa, Nurazizah; Raharjo, Sigit (Jurnal PEKA (Pendidikan Matematika), 2025)
This study aims to analyze the effectiveness of using triangle-shaped teaching aids in improving students' learning outcomes in geometry concepts, particularly triangles. The research employed a quasi-experimental approach with a "Nonequivalent Posttest-Only Control Group" design to evaluate differences in learning outcomes between the experimental and control groups. The sample comprised eighth-grade students at MTS Buaran Tangerang, divided into two groups: the experimental group using teaching aids and the control group following conventional methods. Data were analyzed using normality tests, Pearson correlation tests, and t-tests. The findings reveal that using triangle-shaped teaching aids significantly enhances students’ understanding of triangle concepts. The experimental group achieved higher average learning outcomes compared to the control group. Correlation analysis indicated a strong positive relationship between the use of teaching aids and students' learning outcomes. This study concludes that triangle model teaching aids serve as an effective learning medium to facilitate understanding of abstract mathematical concepts. The findings underscore the importance of innovation in educational tools to support more interactive and meaningful learning processes.